Assessment of quality of life and incontinence in patients of open hemorrhoidectomy - Shweta Pathak ,; Neeraj Kumar Banoria,; Albail Singh Yadav,; Smita Pathak,; Asha Gaud,; Shibin George, (Asian Journal of Medical Sciences, 2024)
Background: For the most part, symptomatic hemorrhoids are a quality-of-life issue. All patients should initially receive conservative management if this fails to improve symptoms, an office-based or operative procedure may be offered. Aims and Objectives: The present study was conducted to assess quality of life using SF-36 health survey and incontinence by Wexner scoring system in patients of open hemorrhoidectomy. Materials and Methods: The study was conducted on 50 cases of open hemorrhoidectomy in M.L.B. Medical College, Jhansi, between January 2021 and June 2022. Results: Results of health-related quality of life in patients before and after open hemorrhoidectomy are compared out of 8 domains, 5 domains, i.e., physical functioning, role limitation due to physical health, social functioning, pain, and general health have significantly shown that patients after open hemorrhoidectomy are having better quality of life before open hemorrhoidectomy. Out of 8 domains, 3 domains such as emotional well-being, vitality, and role limitation due to emotional problems have shown that there is no significant difference in the quality of life in patients before and after open hemorrhoidectomy. Conclusion: Open hemorrhoidectomy patients after open hemorrhoidectomy improved the quality of life of patients treated for hemorrhoidectomy.